A Double Evolutionary Pool Memetic Algorithm for Examination Timetabling Problems. (25th September 2014) - Lei, Yu; Gong, Maoguo; Jiao, Licheng; Li, Wei; Zuo, Yi; Cai, Qing
Abstract : A double evolutionary pool memetic algorithm is proposed to solve the examination timetabling problem. To improve the performance of the proposed algorithm, two evolutionary pools, that is, the main evolutionary pool and the secondary evolutionary pool, are employed. The genetic operators have been specially designed to fit the examination timetabling problem. A simplified version of the simulated annealing strategy is designed to speed the convergence of the algorithm. A clonal mechanism is introduced to preserve population diversity. Extensive experiments carried out on 12 benchmark examination timetabling instances show that the proposed algorithm is able to produce promising results for the uncapacitated examination timetabling problem.